Hg Isotopes and Enhanced Hg Concentration in the Meishan and Guryul Ravine Successions: Proxies for Volcanism Across the Permian-Triassic Boundary - Sial, Alcides Nóbrega; Chen, Jiubin; Korte, Christoph; Pandit, Manoj Kumar; Spangenberg, Jorge E.; Silva-Tamayo, Juan Carlos; Lacerda, Luiz Drude de; Ferreira, Valderez Pinto; Barbosa, José Antônio; Gaucher, Claudio; Pereira, Natan Silva; Riedel, Paulo Ricardo (Frontiers in Earth Science, 2021)
High-resolution organic carbon isotope (δ13C), Hg concentration and Hg isotopes curves are presented for the Permian-Triassic boundary (PTB) sections at Guryul Ravine (India) and Meishan D (China). The total organic carbon (TOC)-normalized Hg concentrations reveal more intense environmental changes at the Latest Permian Mass Extinction (LPME) and the earliest Triassic Mass Extinction (ETME) horizons coinciding with major δ13C shifts. To highlight palaeoredox conditions we used redox-sensitive elements and Rare Earth Element distribution. At Meishan, three Hg/TOC spikes (I, II, and III) are observed. Spike I remains after normalization by total aluminum (Al), but disappears when normalized by total sulfur (TS). Spike III, at the base of Bed 26, corresponds with excursions in the Hg/TS and Hg/Al curves, indicating a change in paleoredox conditions from anoxic/euxinic in the framboidal pyrite-bearing sediments (Bed 26) to oxygenated sediments (Bed 27). At Guryul Ravine, four Hg/TOC spikes were observed: a clear spike I in Bed 46, spike II at the base of the framboidal pyrite-rich Bed 49, spike III at the PTB, and spike IV at the LPME horizon. Some of these Hg/TOC spikes disappear when TS or Al normalization is applied. The spike I remains in the Hg/TS and Hg/Al curves (oxic conditions), spike II only in the Hg/TS curve (anoxic/euxinic), and spikes III and IV only in Hg/Al curves (oxic). In both sections, Hg deposition was organic-matter bound, the role of sulfides being minor and locally restricted to framboidal pyrite-bearing horizons. Positive mass-independent fractionation (MIF) for Hg odd isotopes (odd-MIF) was observed in pre-LPME samples, negative values in the LPME–PTB interval, and positive values above the ETME horizon. Most Hg-isotope patterns are probably controlled by the bathymetry of atmospheric Hg-bearing deposits. The source of Hg can be attributed to the Siberian Traps Large Igneous Province (STLIP). In the LPME-PTB interval, a complex of STLIP sills (Stage 2) intruded coal-bearing sediments. The negative δ202Hg, the mercury odd-MIF Δ201Hg patterns, and the Δ199Hg–Hg plot in both sections are compatible with volcanic mercury deposition. Our study shows the strength of Hg/TOC ratios as paleoenvironmental proxy and as a tool for stratigraphic correlation.